Three moss families (Bryopsida: Calymperaceae, Hyopterygiaceae, & Pterobryaceae): new distribution records to bryoflora of Andhra Pradesh, India - Ananthaneni Sreenath; Midigesi Anil Kumar; Paradesi Anjaneyulu; Ravi Prasad Rao Boyina (Journal of Threatened Taxa, 2020)
Our investigation of the bryoflora of Andhra Pradesh carried out during 2015–19 resulted in three new records of moss families: Calymparaceae, Hypopterygiaceae, and Pterobryaceae represented by Calymperes tenerum, Hypopterygium tamarisci, and Pterobryopsis acuminata, respectively.